Perancangan Aplikasi Kumpulan Resep Masakan Dengan Menerapkan Algoritmaternary Comma Code (TCC) - Kholijah, Siti (Management of Information System Journal, 2023)
Application design has increased very rapidly from year to year. One example is an application in the culinary field. Application design can get cooking recipe applications, especially traditional dishes. In the beginning, many recipes were compiled into a recipe book. However, as technology develops, considering how easy it is for people to get various kinds of information, a smartphone application was created. In designing this application, the author used the Ternary Comma Code algorithm for its development. Cooking recipes are really needed as a tool that can guide when preparing cooking ingredients, how to make them and how to serve them in order to produce dishes with delicious and attractive flavors. Ternary Comma Code is a problem solving approach that emphasizes the role of previous experience. New problems can be solved by reusing and perhaps adapting problems that have similarities to those that have been solved previously. This application provides a search feature and recommendations for suitable recipes based on the cooking ingredients available in the user's kitchen using the Ternary Comma Code method. Based on the results of system functional testing, all respondents agreed that the application created functioned as it should.